The Wentzel-Kramers-Brillouin approximation for light scattering by horizontally oriented prismatic particles. (26th March 2021) - Tari, E M; Bahaoui, A; Lamsoudi, R; Khouilid, M; Ibnchaikh, M
Abstract: In this research, we propose a simple approximation technique based on the decomposition of particles and on the Wentzel-Kramers-Brillouin approximation (WKB). The latter allows us to express analytically the expression of the form factor of a particle of a regular prismatic ice crystal shape. Our focus will be on studying the light scattering by horizontally oriented prismatic particles which rotate about their principal axes. To illustrate our formalism, a few numerical examples will be analyzed.